Laboratory-scale gasification of brown coal and char from RDF pyrolysis - Sebe, Emese; Nagy, Gábor; Kállay, András Arnold (International Journal of Engineering and Management Sciences, 2019)
The pyrolysis is a promising process for producing syngas from wastes. However, the by-product of the technology may contain large quantities of carbon, therefore it is suitable for further syngas production. In this paper we examined the steam gasification of brown coal from Felsőnyárád and char from RDF pyrolysis derived from an experimental pilot plant operating in Zalaegerszeg. We performed our experiments in a laboratory-scale fix-bed reactor at 900 °C. The aim of this work to examine the efficiency of syngas production from pyrolysis char, as well as to explore the similarities and differences of the thermal decomposition of the feedstock materials.